JURNAL NASIONAL TEKNIK ELEKTRO DAN TEKNOLOGI INFORMASI: Desain Metode Polar Fuzzy Vault untuk Proteksi Data Sidik Jari - Yohanes I. Riskajaya, Tohari Ahmad (Teknik elektro UGM, 2017)
Authentication concept using password or token has been used widely but still has weaknesses, because password or token can be easily forgotten or shared with other users. The use of biometric data as an authentication tool can be a solution to the problem. It is because biometric data is relatively permanent and unique, thus, the risk of losing or forgetting the password is reduced. Consequently, a protection method to secure the biometric data is needed. A number of studies have been done to secure the biometric data, ranging from classic encryption method to data transformation.